Haematological and biochemical reference intervals for farmed channel catfish - Tavares-Dias, M.; Moraes, F. R. (Blackwell Publishing, 2007)
The reference intervals for biochemical variables and red blood cell indices of healthy intensively bred channel catfish Ictalurus punctatus were determined. The blood variables were determined using standardized clinical methods. The reference intervals (25th and 75th percentiles) were established using a non-parametric method. Reference intervals for plasma glucose, serum total protein, sodium, potassium, calcium, magnesium, chloride concentration, primary and secondary red blood cell indices were established. The haematological and biochemical reference intervals established may allow important clinical decisions about channel catfish. (c) 2007 the Authors Journal compilation (C) 2007 the Fisheries Society of the British Isles.
Keywords: Blood; channel catfish; Hematology; Ictalurus punctams; reference intervals